2014
DOI: 10.7306/gq.1159
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur isotopes in anhydrite from Badenian (Middle Miocene) salts of the Hrynivka area (Ukrainian Carpathian Foredeep)

Abstract: 1 Na tional Acad emy of Sci ences of Ukraine, In sti tute of Ge ol ogy and Geo chem is try of Com bus ti ble Min er als, Naukowa 3A, 79060 Lviv, Ukraine 34 S is +21.4 ± 0.3‰. Those val ues are sim i lar to those of the Neo gene ma rine sulphates. Com par i son to other geo chem ical data (chem i cal com po si tion of the brine con tained in fluid in clu sions and the bro mine con tent in ha lite) sug gests that the Badenian Carpathian Foredeep evaporite ba sin was sup plied pre dom i nately by sea wa ter sol u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The chemical composition of primary brine, originating fluid brines of the Huwniki-1 well, corresponded more closely to the geochemical characteristics of brines collected in the eastern segment of the Carpathian Foredeep-e.g., at Hrynivka [62] or Slanic-Prahova [46]. Upon comparison of these results with the results of the chemical composition of modern seawater (Table 1, Figure 7), it was concluded that the former contained slightly fewer sulfate ions.…”
Section: Discussionmentioning
confidence: 91%
“…The chemical composition of primary brine, originating fluid brines of the Huwniki-1 well, corresponded more closely to the geochemical characteristics of brines collected in the eastern segment of the Carpathian Foredeep-e.g., at Hrynivka [62] or Slanic-Prahova [46]. Upon comparison of these results with the results of the chemical composition of modern seawater (Table 1, Figure 7), it was concluded that the former contained slightly fewer sulfate ions.…”
Section: Discussionmentioning
confidence: 91%
“…The fluc tu a tion in the ob served iso tope val ues of anhydrite can be ex plained by chem i cal and bi o log i cal pro cesses dur ing sed i men ta tion and early diagenesis in the evaporite ba sin (Pankina et al, 1985;Shekhunova and Stadnichenko, 2010;Galamay et al, 2014). There fore, frac tion ation in d 34 S and d…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…The ex ten sive de velop ment of bac te rial sul phate re duc tion con trib uted to a high alka lin ity of brine (Galamay et al, 2013) and a high con tent of organic mat ter bur ied in sed i ments. For ex am ple, the de fi ciency of such fac tors was the cause of the poor de vel op ment of bac terial sul phate re duc tion in the Badenian sa line bas ins Galamay et al, 2014).…”
mentioning
confidence: 99%
“…Hence, de tailed sedimentological, pet ro log i cal, min er al og i cal, iso to pic and fluid in clu sion stud ies on the Up per Badenian and Sarmatian rocks from south east ern Po land and west ern Ukraine have been carried out in the last two de cades (e.g., Dziadzio, 2000;Maliszewska et al, 2001aMaliszewska et al, , b, 2004Jasionowski and Peryt, 2010;Jarmo³owicz-Szulc et al, 2011;Koz³owska et al, 2011;Kuberska et al, 2011;Lis and Wysocka, 2012;Jasionowski et al, 2012;Wysocka et al, 2012;Peryt et al, 2014;Galamay et al, 2014). Iso to pic anal y sis and par tic u larly stron tium iso to pic anal y ses have proven a pow er ful chronostratigraphic tool (e.g., McArthur et al, 2001, with ref er ences therein).…”
Section: Introductionmentioning
confidence: 99%